2020
DOI: 10.1002/mabi.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Ultrasound Activated Lipopolyplexes for Enhanced Transfection by Low Frequency Ultrasound in In Vitro Tumor Model

Abstract: This work focuses on the development of ultrasound contrast vesicles for ultrasound‐mediated enhanced transfection of nucleic acids in the cancer cells and projects its application as a tool for diagnostic imaging. The ultrasound contrast vesicles are stable, anionic, nanoscaled vesicles with ultrasound contrast equivalent to the commercially available SonoVue. These anionic lipid vesicles establish electrostatic interaction with cationic polyplexes based on linear polyethylenimine (22kDa) forming lipopolyplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…From our experiment, it was observed that the lipid covering of dendriplexes enhanced the penetration and gene expression of the nanocarrier system in the spheroidal matrix system and demonstrated a superior GFP expression while a lower transfection efficiency was observed with the naked dendriplexes system (Fig. 5a) 45 . The results obtained with multicellular spheroid coincide with that observed in the 2D culture of HEK-293 cells.…”
Section: Resultsmentioning
confidence: 72%
“…From our experiment, it was observed that the lipid covering of dendriplexes enhanced the penetration and gene expression of the nanocarrier system in the spheroidal matrix system and demonstrated a superior GFP expression while a lower transfection efficiency was observed with the naked dendriplexes system (Fig. 5a) 45 . The results obtained with multicellular spheroid coincide with that observed in the 2D culture of HEK-293 cells.…”
Section: Resultsmentioning
confidence: 72%
“…Ultrasound was first used in the mid‐1990s to mediate the in vitro transfection of DNA. [ 237 ] It was not until 2000 that ultrasound was used in vivo to transfer nucleic acid molecules to muscle, [ 238 ] solid tumor, [ 239 ] liver, [ 240 ] kidney, [ 241 ] and heart. [ 242 ] This method can realize the gene transfection of visceral organs [ 243 ] without surgery, and the use of ultrasound contrast agent or microbubbles filled with compressed air can further improve the gene expression level.…”
Section: Non‐viral Vectors For Nucleic Acid Deliverymentioning
confidence: 99%
“…Another unusual approach focuses on improving the lipopolyplex cellular uptake via local use of low-frequency ultrasound (3 MHz) [ 121 ]. In in vitro studies such a procedure allows better penetration of the proliferating (outermost) layers of 3D spheroid culture of ovarian cancer SKOV-3 cells by vesicles carrying both an ultrasound contrasting agent (inside the carriers) and PEI-based polyplexes (present on the surface), even in the presence of endocytosis inhibitors.…”
Section: Possible Directions Of Development Of Lipopolyplexesmentioning
confidence: 99%